If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7 = 58 + -7x Reorder the terms: 7 + 6x = 58 + -7x Solving 7 + 6x = 58 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 7 + 6x + 7x = 58 + -7x + 7x Combine like terms: 6x + 7x = 13x 7 + 13x = 58 + -7x + 7x Combine like terms: -7x + 7x = 0 7 + 13x = 58 + 0 7 + 13x = 58 Add '-7' to each side of the equation. 7 + -7 + 13x = 58 + -7 Combine like terms: 7 + -7 = 0 0 + 13x = 58 + -7 13x = 58 + -7 Combine like terms: 58 + -7 = 51 13x = 51 Divide each side by '13'. x = 3.923076923 Simplifying x = 3.923076923
| 6x-2=16x-34 | | 1x+1x=4x | | 15x-7=11-12x | | 99999x+9998888x=1 | | 104-4x=4x+8 | | 8x+900x=26-9 | | 21+2x=5x+3 | | 8x+2=11x+7 | | 2x+3=-4x-7 | | -9x-4x=9-7x | | 8a+4b+4a= | | x+6y=-47 | | 117-6x=12x+15 | | (x+1)(3x+1)=(2x)(14-3x)+(x+1) | | y=x^2-x-1 | | 26w+182=260 | | 35+15c=200 | | 10x=8x+16 | | 2p+34=46 | | 5x-1=5x-5 | | 3s+24=90 | | -6=4b-10 | | 4x^2-17=5x^2+18x | | 6y^2=3y | | y=-17 | | 2(x+3)2=5(x+3)-2 | | 1+4ln(2x)=17 | | 6x-5=13x-24 | | 2y-3=-11 | | 24a^2-6ab-3b^2=0 | | 6x=28 | | 202-4x=32x+18 |